Perception of retailers and INPEV collection centers in the region of Alta Paulista (state of São Paulo), as participants of reverse logistics of agrochemical packaging - Marques, Maurício Dias; Braga Junior, Sergio Silva; Merlo, Edgard Monforte; Martinez, Marta Pagán (Sustainability in Debate, 2016)
This article seeks to understand how retailers and collection centers participate in the reverse logistics linked to the collection of empty pesticide containers. Based on documentary and bibliographical research on the legislation that mandates reverse logistics, field research was conducted by means of the application of questionnaires to four retailers and two collection center managers, active in the agricultural region of Alta Paulista, in the interior of the state of São Paulo. The objectives were (i) to determine how these agents perceive the reverse logistics procedures linked to the collection of pesticide packaging mandated by Brazilian law and (ii) their roles in these procedures. It was found that (i) respondents try to comply with the law despite operational failures linked to the lack of physical infrastructure and to gaps in the legislation with regard to controls over container returns and (ii) that these problems could be solved with government support.